Redefining Transformation Drivers in SMEs toward Business Performance with Covid-19 Situation in Indonesia - Primadana, Ligasyah Arnanda; Ramdani, Muhammad Abdilah; Sahara, Shifa Hustima; Aprianingsih, Atik (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
The purpose of this study is to understand transformation drives using past research as the basis of argument on every variable with business performance as the measurement standard. The research using deep searching of journal databases, the output is conducting a conceptual framework. The transformation drivers in our conceptual framework have six factors namely organization, technology, consumer behavior, financial, external support, and network with the measure of success of that transformation drives using business performance. The result is that the past research supports all the purposes of points in the variable that can positively contribute to business performance.